2009
DOI: 10.1186/1477-7827-7-91
|View full text |Cite
|
Sign up to set email alerts
|

"hCG priming" effect in controlled ovarian stimulation through a long protocol

Abstract: Background: Recently, it has been demonstrated that, in patients down-regulated by GnRH analogues (GnRHa), a short-term pre-treatment with recombinant LH (rLH), prior to recombinant FSH (rFSH) administration, increases the number of small antral follicle prior to FSH stimulation and the yield of normally fertilized embryos. However, no data exist in the literature regarding the potential beneficial effect of "hCG priming" in controlled ovarian hyperstimulation (COH) through a long GnRH-a protocol, which binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 43 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…Statistical significance was set at a P value <.01. We evaluated the degree of variation across studies attributable to heterogeneity with the I 2 statistic [17]. We conducted the meta-analysis using Review Manager software …”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance was set at a P value <.01. We evaluated the degree of variation across studies attributable to heterogeneity with the I 2 statistic [17]. We conducted the meta-analysis using Review Manager software …”
Section: Discussionmentioning
confidence: 99%
“…Further studies are, therefore, required to examine the possible effects of longer and/ or more powerful pretreatments using higher doses of LH or hCG, a hormone whose biopotency is higher than that of LH. Indeed, in pilot studies, some investigators have obtained encouraging results with the use of hCG instead of LH before COH (42,43).…”
Section: Leuteinizing Hormone Activity Administrationmentioning
confidence: 96%
“…Yet, this approach depends on the amount of androgens that effectively become available to ovarian follicles. The other approach that can be used to increase intraovarian androgen availability is to stimulate thecal production by administering LH activity (LH or hCG) (41)(42)(43). A third possibility to increase intraovarian androgens is the use of aromatase inhibitors (44)(45)(46)(47) to prevent androgen metabolism into estrogens.…”
Section: Androgens and Folliculogenesis: Therapeutic Perspectivesmentioning
confidence: 98%
“…Two studies have reported the use of hCG in the early follicular phase of ovarian stimulation (100,101). These trials and two case reports have used various dosing strategies to deliver the hCG, including 200 IU per day for four or seven days, 50 IU per day for 14 days, and 1,250 IU in a single dose on cycle day two (100-103).…”
Section: Human Chorionic Gonadotropinmentioning
confidence: 99%